Effects of maturity stages at harvest, packaging materials and storage duration on physico-chemical characteristics of lemongrass (cymbopogon citratus stapf) - Tajidin, Nor Elliza (2012)
Lemongrass, a perennial and lemon-aromatic grass, is harvested normally at 4 to 8 months after planting. There is a lack of information on its harvesting time for commercial production. Harvesting at the right maturity stages will give satisfactory biomass yield, high citral and nutritional content. Longer storage duration for pseudostem causes the formation of red pigmentation, wilting and the reduced lemon aroma. The first experiment was to determine the optimum maturity stages at harvest by using plant growth indicator and citral content of lemongrass. Lemongrass was planted at the Universiti Agricultural Park, Universiti Putra Malaysia, Serdang, Selangor, using a randomized complete block design (RCBD) with four replications. Harvestings were done at 5.5, 6.5, and 7.5 months after planting. There were quadratic relationships between clump gross and dry matter weights and maturity stages of lemongrass plants. There were linear increases in both the weights when the plants were harvested at 6.5 compared to 5.5 months, followed by gradual decreases at 7.5 months after planting. Clump height and leaf blade showed significant linear increases as maturity advances. However, pseudostem length showed a quadratic increase when lemongrass was harvested between 5.5 to 7.5 months after planting. Total tiller weight and tiller number showed similar quadratic relationships as clump gross and clump dry matter weights. N contents in leaf blade and pseudostem showed quadratic decreases as maturity advances. There were quadratic increases in P, K, Ca and Mg content of lemongrass when harvested at 6.5 months compared to 5.5 months after planting. However, the nutrients in the leaf blade and pseudostem were decreased when the lemongrasses were harvested at 7.5 months after planting. There were significant effects of maturity stages on citral contents of lemongrass. Thirteen compounds always were detected at each maturity stage. The citral contents of lemongrass harvested were higher at 6.5 months after planting compared to at 5.5 and 7.5 months, respectively, after planting. Citral content was highest at 7± 0.3 months after planting, when it reached 78%. The results indicated that the correlations between citral content and clump characters such as clump gross weight (r=0.86) and clump dry matter weight (r=0.88) were significantly positive. Also, there were significant and positive correlations between citral content and pseudostem length (r=-0.80), and total tiller weight (r=0.82) and total tiller number (r=0.89) per clump. The correlation coefficients between the citral content and percentage of major nutrient concentrations in leaf tissues, such as P (r=0.75) and K (r=0.78) were significantly positive, and so were the minor nutrient such as Ca (r=0.67) and Mg (r=0.69). These correlations indicated that any of these characters could be used as an indicator for citral content in lemongrass. The second experiment was carried out to determine the effects of maturity stages at harvest, packaging materials and storage duration on the physico-chemical characteristics of lemongrass. At 5.5, 6.5 and 7.5 months after planting, the lemongrass pseudostems were cut to 20 cm in length. Then, five pseudostems were packed into two types of packaging materials; black and clear polyethylene (PE) bags. Bags were sealed, then were stored at 10 0C. The physico-chemical characteristics of the lemongrass were evaluated for firmness, chlorophyll, anthocyanin, ascorbic acid, and total phenolic contents, soluble solids concentration, titratable acidity, and pH. Measurements were made at 0, 5, 10 and 15 days after storage. Results indicated that there were no interaction effects between the treatments on firmness, ascorbic acid, titratable acidity and pH. Firmness increased as maturity stage advances from 5.5 to 7.5 months after planting, but decreased as storage duration increased. Both ascorbic acid and titratable acidity decreased with increased in maturity stages and storage duration. However, pH of lemongrass decreased with increasing maturity, but the pH was not affected by storage durations. During the storage, data showed that firmness, ascorbic acid, titratable acidity and pH were not affected by the use of the clear and black polyethylene (PE) packaging materials (bag). Chlorophyll content of lemongrass harvested at 5.5, 6.5 and 7.5 months after planting tended to decrease during storage. In contrast, the anthocyanin content increased when the storage duration was increased, but it was lower in pseudostem that were packed in black PE bag then those packed with clear PE bag. There was a significant interaction effect of maturity stage at harvest and storage duration of lemongrass on total phenolic content of lemongrass pseudostems. Total phenolic content increased by 35.90%, 35.80% and 56.52% when lemongrass was harvested at 5.5, 6.5 and 7.5 months after planting, respectively, as storage duration increased to 15 days of storage. By the end of the storage duration, lemongrass harvested at 7.5 months after planting contained the highest total phenolic content compared to those harvested at 5.5 and 6.5 months after planting. In conclusion, this study showed that maturity stage at harvest influenced the plant growth characteristics, essential oil composition and citral content of lemongrass. The packaging materials used to wrap the lemongrass pseudostems during storage significantly affected the total phenolic content of lemongrass. The anthocyanin content of lemongrass harvested at 5.5 months was less than the other lemongrasses harvested at 6.5 and 7.5 months after planting. The anthocyanin caused the red pigmentation on lemongrass pseudostem. The pseudostem were less firm, and had a lower content of total phenolic when harvested at 5.5 months compared to those harvested at 6.5 and 7.5 months after planting. Longer storage duration increased soluble solids concentration, and anthocyanin and total phenolic contents, which are indicators of senescence process. Losses of ascorbic acid were high as the storage duration increased. Thus, lemongrass should be harvested between 6.5 to 6.9 months after planting to obtain optimum growth performance and essential oil with a high composition of citral.